La COVID-19 y la adopción de políticas financieras económicas de recuperación de la empresa de transportes Caipo SRL 2020 - Rubio Sandoval, Violeta Isabel (2021)
The general objective of the research was to determine the relationship between COVID-19 and the economic financial policies for the recovery of Empresa de Transportes Caipo SRL 2021; in this sense, the study responds to the need to know the consequences that the pandemic produced in the company and from there to generate its recovery, through the cause-effect relationship between COVID-19 and the economic financial policies. The research hypothesis is, the Adoption of Economic Financial Policies before the Covid-19 does allow the positive Recovery of the Company Transportes Caipo SRL - 2020 after evaluating the effect of the COVID-19. The methodology is descriptive analytical. it is concluded, that the referred company was affected both in the economic and financial situation, as demonstrated in the table nº22 of results; however, the Management knew how to adopt the pertinent measures by modifying its sales through the transfer of personnel to mining companies in Pataz, reducing its frequency of interprovincial transport of passengers, to such an extent that it generated higher profit than the year 2019. Likewise I conclude that effectively COVID -19 has a direct relationship in the adoption of financial and economic policies that implies the recovery of the entity; with a good financial position, and regular economic position, the top management of the company should maintain its policies that it established at the beginning of the pandemic.